La gouvernance parisienne, un objet de débat public ? - Arnaud Brennetot (L'Espace Politique)
The media coverage given to the presidential projects related to Greater Paris contributes to making urban governance a new object of public debate. Beyond the technical issues pertaining to decision making, a geoethical analysis of the statements made by political actors in the French press highlights the existence of diverging ideological currents as regards spatial justice and ideal urbanity: while the right conveys a rather neoliberal vision of Greater Paris, which it justifies by the necessity to adapt to the competition between territories, the left favours social cohesion and territorial equity. This political split appears to be a condition of the politicization of the governance of Paris.